Dissociative or associative cognitions: a focus on muscle pain can be more effective for muscular endurance performance. Issue 6 (2nd November 2022) - Denis, Gauthier; Radel, Rémi; Deshayes, Maxime; Zory, Raphael
ABSTRACT: The perception of painful bodily sensations is usually negatively associated with endurance performance, and dissociative strategies are routinely recommended to divert attention away from these signals. The effectiveness of dissociative strategies has not been clearly established, but associative strategies seem to benefit physically trained individuals. The purpose of this study was to clarify and compare the effects of these two strategies on the maintenance of physical effort in a physically active population. We hypothesised that an associative focus would increase endurance performance more than a dissociative focus. The participants (572: 161 women and 411 men) performed muscular endurance tasks until exhaustion in associative and dissociative conditions. The aerobic fitness level could be tested in 285 participants using a maximum aerobic speed field test. To perform additional statistical analyses, two fitness-level groups were created based on the median. Our results showed that participants performed better in the associative condition than the dissociative condition, and complementary analyses revealed that association specifically improved performance in the higher aerobic fitness group. These results suggest that monitoring afferent painful signals could be an interesting attentional strategy and that individuals can develop abilities to tolerate and apprehend this sensory feedback. These results are discussed in relation to a recent interoceptive model of physical effort.